The intestinal microbiome and the leaky gut as therapeutic targets in alcoholic liver disease - Hartmann, Phillipp; Chen, Wei-Chung; Schnabl, Bernd (Frontiers in Physiology, 2012)
Alcoholic liver disease (ALD) encompasses hepatic steatosis, which may progress to alcoholic hepatitis, fibrosis, and cirrhosis. It remains a leading cause of morbidity and mortality in the US and worldwide. The severity of liver disease correlates with plasma levels of bacterial products in patients, and experimental ALD depends on the level of gut derived bacterial products in rodents. Since intestinal decontamination and deficiency of bacterial product receptors or their downstream signaling molecules protect from alcohol-induced liver disease, bacterial translocation (BT), qualitative, and quantitative changes of the enteric microbiome are considered as being of fundamental importance in the pathogenesis of ALD. Recent enhancements in diagnostic technologies provide a better insight into these shifts. This review highlights vital events in ALD such as BT, the importance of Toll-like receptor (TLR) signaling, intestinal bacterial overgrowth (IBO), and changes in the intestinal microbiome. Furthermore, a treatment trial section of patients reviews possible future options of therapy for ALD modifying the enteric microbiome.